Hypocenter Relocation using Teleseismic Double Difference Method (Case Study: West Sulawesi, Indonesia) - Harmita Lestari; Pepen Supendi; Andri Dian Nugraha; Wira Hadi Kusuma (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2026)
This study analyzes seismicity in West Sulawesi through earthquake hypocenter relocation using the teleseismic double-difference (TeletomoDD) method. P-wave arrival times recorded by local, regional, and teleseismic stations from the Meteorology, Climatology, and Geophysics Agency (BMKG) were analyzed for the period January 2017 to January 2021. The hypocenter relocation results show a significant reduction in residual time, with most values concentrated between −10 and 10 before relocation and more than 50% near zero after relocation. The epicenters shifted toward the northwest and southeast, driven by the complex tectonic conditions and the presence of shallow faults, particularly along the Mamuju–Mamasa at depths of 5 km to 10 km. The average horizontal hypocenter shift was approximately 4.9 km relative to the routine BMKG catalog, with maximum corrections reaching approximately 17.7 km, and roughly 37.5% of events showing shifts 4-5 km, indicating a substantial improvement in the spatial accuracy of the original catalog. The seismicity analysis results indicated that the fault area was dominated by shallow earthquakes with an average earthquake magnitude of M > 4. The local tectonic regime, mainly controlled by an active shallow crustal thrust fault, suggests that the majority of seismic events are related to local faulting, although some mechanisms remain uncertain. The relocated hypocenter distribution obtained in this study indicates relatively high seismicity in the region. These findings provide improved constraints on seismicity patterns and fault geometry in West Sulawesi, which are important for understanding regional tectonics in more detailed.